The Experiences of Nursing Students Who Attended Hospital Clinicals During the COVID‐19 Pandemic: A Qualitative Study - Yasemin Özer Güçlüel; Gülcan Kendirkiran; Pelin Gökoğlu Gürer (Nursing Open)
ABSTRACT Aim This study examined the experiences of nursing students who attended hospital clinicals during the COVID‐19 pandemic. Design Study was conducted in a descriptive design. Methods A total of 21 nursing students from the second, third and fourth grades who attended hospital clinics in the spring semester of the 2020–2021 academic year and volunteered to participate in the study were included in the study. Purposive sampling method was used in the study. The themes obtained through content analysis of the interviews were listed and sub‐themes were created. The NVivo computer program was also used in the analysis of the study data. Results A total six main themes were identified in this study. These main themes are the psychological effects of COVID‐19 on students, the effects on their families, the effects on their clinical practice, the students' perspectives on the profession, the behaviours of the staff in the clinical area and the behaviours of patients/patient relatives. Patient or Public Contribution Today, different crisis situations such as pandemics can be encountered. It is important to understand and analyse the experiences of nursing students in difficult and crisis situations. It is clear that the psychological effects on nursing students are high in crisis situations. This study can form a basis for many factors such as preventing stress‐related problems in students in crisis situations, preventing them from leaving the profession and developing a positive view of the profession.